2003
DOI: 10.1007/s11738-003-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of jasmonic acid on the accumulation of ABA, proline and spermidine and its influence on membrane injury under water deficit in two barley genotypes

Abstract: Seedlings of two barley genotypes ('Maresi' and wild form ofHordeum spontaneum) were treated with jasmonic acid (JA 5 laM and 15 laM) for 24 h, and then subjected to water stress (PEG 6000 solution of-1.5 MPa). JA caused an increase in the content of ABA but not in that of proline and spermidine in the two studied genotypes. The effect of the treatment did not depend on the applied JA concentration. The pre-stress treatment with JA changed plant response to water deficit with regard to membrane injury. Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 38 publications
6
47
1
Order By: Relevance
“…Drought stress increased membrane leakage in Ocimum basilicum L. [14]. JA application protects membranes from damage by various stress factors by reducing MDA content [23]. From present study it was observed that this protection of cell membrane by JA is very much dose dependent along with absence or presence of any stress factor such as copper in present case.…”
Section: +supporting
confidence: 55%
“…Drought stress increased membrane leakage in Ocimum basilicum L. [14]. JA application protects membranes from damage by various stress factors by reducing MDA content [23]. From present study it was observed that this protection of cell membrane by JA is very much dose dependent along with absence or presence of any stress factor such as copper in present case.…”
Section: +supporting
confidence: 55%
“…According to the cited authors, JA protects seedlings from stress damage by stimulating antioxidant enzymes and increasing antioxidant levels. The protective role of jasmonates against lipid peroxidation induced by abiotic stress was also reported in other studies [15,35,36].…”
Section: Fatty Acids Ratiosupporting
confidence: 76%
“…In soybean, exogenous application of MeJA did not affect endogenous ABA levels, but waterstressed barley seedlings pretreated with JA showed more than 4-fold accumulation of ABA in comparison to water stressed-barley seedlings not pretreated with JA. This indicates a role for JA in ABA biosynthesis under water stress conditions (Bandurska et al 2003). Many droughtresponsive genes are regulated by MeJA (Huang et al 2008) and several MeJA-regulated, drought-responsive genes are also regulated by ABA with similar expression kinetics (Huang et al 2008;Nemhauser et al 2006).…”
Section: Jasmonatesmentioning
confidence: 89%